A Narrative Review of the Ocular Manifestations in Noonan Syndrome. (17th February 2022) - Christou, Evita Evangelia; Zafeiropoulos, Paraskevas; Rallis, Dimitrios; Baltogianni, Maria; Asproudis, Christoforos; Stefaniotou, Maria; Giapros, Vasileios; Asproudis, Ioannis
ABSTRACT: Purpose: The purpose of this review is to provide an update on ophthalmological manifestations of Noonan Syndrome (NS). Emerging evidence has suggested that NS patients may present with a wide spectrum of ocular characteristics. Detailed investigation of genotype has revealed the diversity of related gene mutations. The potential association of genetic basis with clinical expressivity of phenotype remains a challenging aspect of this issue. Methods: A literature search was performed in PubMed; we have analyzed prospective and retrospective cohort studies, case reports, and reference lists of retrieved articles until February 2021. We identified all papers referring to NS ocular manifestations referring to genotype and phenotype characteristics. Results: A comprehensive update on ocular manifestations of NS patients indicates significant evidence for variability of genotype and phenotype features. Ophthalmologic features of NS are characterized by a wide spectrum of abnormalities; external ocular malformations, distortions of refraction, alignment, motilily, anterior and posterior ocular segment and visual impairment. Currently, a variety of pathogenic mutations in patients with NS have been investigated, while the nature of the genetic variants may determine expressivity. Albeit it remains a clinical diagnosis with variation in the progress of each NS phenotype. Although the available evidence that is needed to establish genotype-phenotype correlation as predicting factor in clinical practice is limited, it could aid risk assessment and patient management. Conclusion: A review of the existing literature sheds light on the ocular characteristics of NS. The current article discusses notable aspects of key publications on the topic, highlights the importance of the potential genotype-phenotype correlation in clinical practice, and proposes the need for further future research.